RNA modifications modulate activation of innate toll-like receptors - Freund, Isabel; Eigenbrod, Tatjana; Dalpke, Alexander (Genes, 2019)
Self/foreign discrimination by the innate immune system depends on receptors that identify molecular patterns as associated to pathogens. Among others, this group includes endosomal Toll-like receptors, among which Toll-like receptors (TLR) 3, 7, 8, and 13 recognize and discriminate mammalian from microbial, potentially pathogen-associated, RNA. One of the discriminatory principles is the recognition of endogenous RNA modifications. Previous work has identified a couple of RNA modifications that impede activation of TLR signaling when incorporated in synthetic RNA molecules. Of note, work that is more recent has now shown that RNA modifications in their naturally occurring context can have immune-modulatory functions: Gm, a naturally occurring ribose-methylation within tRNA resulted in a lack of TLR7 stimulation and within a defined sequence context acted as antagonist. Additional RNA modifications with immune-modulatory functions have now been identified and recent work also indicates that RNA modifications within the context of whole prokaryotic or eukaryotic cells are indeed used for immune-modulation. This review will discuss new findings and developments in the field of immune-modulatory RNA modifications.
Gesehen am 16.05.2019